Fostering Critical Thinking in Academic Writing through a Meta-Reflective Model: Integrating Self-Assessment and Inquiry-Based Learning - Harsono, Harsono; Amalia, Laili; Sanulita, Henny; Aticqa, Emas Malika Balqies Putri; Rahmatullah, Affan Maulidi (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
Academic writing in higher education requires students to demonstrate critical and reflective thinking skills. However, writing instruction rarely provides a systematic model that integrates metacognitive reflection into the writing process. This gap causes students to experience difficulties in linking self-reflection with the development of academic argumentation. This study aims to develop and examine the effectiveness of a meta-reflective writing model that integrates self-assessment and inquiry-based learning to enhance students’ critical thinking skills. The study employed a research and development (R&D) approach encompassing a preliminary study, model design, expert validation, limited trials, and effectiveness testing. The participants consisted of two expert validators and 20 students enrolled in a language education program. Validation results indicated that the model was highly feasible, with a mean score of 4.47. Findings from the limited trials demonstrated improvements in the quality of students’ written argumentation. Effectiveness testing using a one-group pretest–posttest design revealed a statistically significant increase in critical thinking scores from 22.1 to 44.4 (p < 0.001).These findings confirm that the meta-reflective writing model is effective, practical, and relevant as a pedagogical approach for strengthening critical thinking in academic writing, although further refinement of indicators at the pre-writing stage is still required.